Implementation of a Patient-Provider Agreement to Improve Healthcare Delivery for Patients With Substance Use Disorder in the Inpatient Setting. Issue 8 (8th December 2021) - Wurcel, Alysse G.; Yu, Sun; Burke, Deirdre; Lund, Amy; Schelling, Kim; Weingart, Saul N.; Freund, Karen M.
Abstract : Objectives: Inpatient healthcare delivery to people who use drugs is an opportunity to provide acute medical stabilization and offer treatment for underlying substance use disorder (SUD). The process of delivering quality healthcare to people with SUD can present challenges. Methods: We convened a group of stakeholders to discuss challenges and opportunities for improving healthcare safety and employee satisfaction when providing inpatient care to people with SUD. Results: We developed, implemented, and evaluated a "Pain and Addiction Agreement" tool, a document to guide discussions between providers and patients about expectations and policies for inpatient care. Conclusions: In this article, we share our experience of working closely with stakeholders. We hope that our project can serve as a blueprint motivating other centers to pursue quality improvement initiatives to improve healthcare for people with SUD and support the people who take care of them in the hospital.